Machine Learning-Based Sentiment Analysis on Twitter (X): A Case Study of the “Kabur Aja Dulu” Issue Using SVM - Rohmatun, Lina; Baita, Anna (Journal of Applied Informatics and Computing, 2025)
This study aims to analyze public sentiment toward the phenomenon of “Kabur Aja Dulu” on Twitter (X) using the Support Vector Machine (SVM) method. The data used consists of 4,768 Indonesian-language tweets collected through web scraping. The pre-processing process includes data cleaning, tokenization, stemming, and translation into English for automatic sentiment labeling using TextBlob. The data is then classified into three sentiment categories: positive, negative, and neutral. To address class imbalance, the SMOTE method is applied to the training data, along with TF-IDF techniques for feature extraction. The model was evaluated using the K-Fold Cross Validation method and Grid Search for hyperparameter tuning. The results of the study show that the SVM model with a linear kernel and parameter C=10 provides the best performance with an accuracy value of 85.56%, precision of 845.19%, recall of 85.56%, and F1-score of 85.30%. The main finding of this study is that the linear SVM method is capable of classifying sentiment well, particularly for neutral sentiment data, and has proven effective as an approach to sentiment analysis in the context of social media using the Indonesian language.